Investigation of the growth performance, blood status, gut microbiome and metabolites of rabbit fed with low-nicotine tobacco - Jing, Changliang; Wang, Jiahao; Xie, Yi; Zhang, Jianhui; Guo, Yixuan; Tian, Tian; Tang, Jing; Ju, Fuzhu; Wang, Chunkai; Liu, Yanhua; Zhang, Zhongfeng; Yang, Xingyou; et al. (Frontiers in Microbiology, 2022)
Tobacco contains large amounts of active ingredients which can be used as source of feed. The objective of this study was to evaluate the effects of adding different amounts of tobacco leaf with low nicotine (LNT) to rabbit diets on the growth performance, blood status, gut microbiota composition and metabolite composition of meat rabbits. A total of 80 Kangda white rabbits of similar weight were randomly assigned to the four different groups, feeding a basal diet (control group) and three groups supplemented with 5%, 10% and 20% LNT, respectively. Each treatment had 20 repeats, and all were raised in a single cage. The experiment lasted 40 days with 7 days as a predictive period. The results revealed that LNT supplementation had no significant differences on growth performance, but affected the half carcass weight compared with the control group. Dietary supplemented LNT decreased the serum and cholesterol content in rabbit serum, and the plasma concentration of lymphocytes LYM, lymphocytes LYM, monocytes, eosinophils, hemoglobin HGB and red blood cells were significantly increased. In addition, LNT significantly changed the microbial diversity and richness, and metagenomic analysis showed that LNT significantly increased the genus Eubacterium_siraeum_group, Alistipes, Monoglobus and Marvinbryantia at the genus level. Moreover, LC-MS data analyses identified a total of 308 metabolites that markedly differed between the two groups. 190 metabolites were significantly upregulated whereas the 118 metabolisms were significantly downregulated. Furthermore, through correlation analysis, it was found that there was a significant correlation between differential microbial and rabbit growth performance. Overall, these findings provide the theoretical basis and data support for the application of LNT in rabbits.